Sensing methods for real-time Loop-mediated Isothermal Amplification in Digital Microfluidic systems - Marques, Filipe André da Palma (2019)
Digital Microfluidics (DMF) is a technology capable of maneuvering picoliter to microliter droplets in an independent and individual manner, with a wide variety of uses for bioassays and biosensing. These systems are advantageous for their small volumes, higher portability and multiplex assay capabilities, proving to be very capable of lab-on-chip and point-of-care applications. One of these applications are DNA amplification assays, of which, Loop Mediated Isothermal Amplification (LAMP), that has received increased interest from the scientific community. This method is a sensitive and simple diagnostic tool for fast detection and identification of molecular biomarkers enabling real-time monitoring. Nevertheless, sensing methods coupled with DMF devices are still uncapable of measuring the progress of said reaction in real-time. This work explores two real-time LAMP measurement approaches to be coupled with a DMF system. The first approach uses an H-shaped device, where human c-Myc proto-oncogene and human 18S housekeeping gene are amplified and measured in real-time through fluorescence methods. The second approach uses interdigitated electrodes, where human c-Myc proto-oncogene is amplified and measured in real-time through Electrochemical Impedance Spectroscopy (EIS). Following development and characterization of both techniques, fluorescence measuring devices show 49% fluorescence signal difference between positive and negative controls end-points. EIS measuring devices indicate significant differences between commercial solutions with pH 4, 7 and 10, by Ciclic Voltammetry. This suggests that such devices could be used for real-time, label free, LAMP monitoring, since significant pH changes occur during a LAMP reaction